2016
DOI: 10.1039/c6ra00456c
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of chitosan/silica nanofibrous adsorbent functionalized with amine groups for the removal of Ni(ii), Cu(ii) and Pb(ii) from aqueous solutions: batch and column studies

Abstract: Homogeneous fibers with average diameters of 90 and 138 nm were formed as pure CS and CS/TEOS/APTES nanofibers and the performance of the prepared nanofibers was investigated for Ni(ii), Cu(ii) and Pb(ii) ion sorption.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(12 citation statements)
references
References 33 publications
0
12
0
Order By: Relevance
“…This biopolymer has been used as an adsorbent of various substances, such as metal ions, aromatic compounds, organic and inorganic acids, and colorings. This is due primarily to its structure, which contains hydrophilic and hydrophobic groups, as well as hydroxyls and amines, which confer powerful adsorptive properties [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…This biopolymer has been used as an adsorbent of various substances, such as metal ions, aromatic compounds, organic and inorganic acids, and colorings. This is due primarily to its structure, which contains hydrophilic and hydrophobic groups, as well as hydroxyls and amines, which confer powerful adsorptive properties [ 9 , 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…When the pH values were raised over 5, the –OH groups on the SiO 2 nanoparticle surfaces suggested making the adsorbent membrane surface more negatively charged [48]. Meanwhile, the incorporation of negative functional groups including siloxane, silanol, and amine groups into the SiO 2 @PVDF-HFP fibrous membrane which enhanced the available active sites for adsorption process [48,49]. For one thing, the Cu(II) metal ions with positive charges can easily interact with the surface of electrospun membrane.…”
Section: Resultsmentioning
confidence: 99%
“…The isotherm simulation results are shown in Figure 6c,d, and much more details are presented in Table 2. Making comparison of the correlation coefficients, it was found that the equilibrium data was best described by Freundlich isotherm model ( R 2 = 0.97377) than that from Langmuir isotherm model ( R 2 = 0.92495) [49]. It was caused by the multilayer reaction adsorption of Cu(II) ions onto the heterogeneous surface of multi-structured SiO 2 @PVDF-HFP fibrous membranes, i.e., the stronger binding sites are occupied firstly by the membrane, which is consistent with the mechanism of Freundlich isotherm adsorption [53].…”
Section: Resultsmentioning
confidence: 99%
“…Different methods have been developed for the removal of heavy metals from wastewater including adsorption, chemical precipitation, ion exchange, membrane separation, and electrochemical treatment . However, adsorption process is the most commonly used since ages for cleaning of water.…”
Section: Introductionmentioning
confidence: 99%